Aloe vera extract reduces 8-oxo-2-deoxyguanosine levels and improves total antioxidants in streptozotocin-induced diabetic rats - Christijanti, Wulan; Marianti, Aditya; Isnaeni, Wiwi (Universa Medicina, 2017)
BackgroundDiabetes mellitus is a chronic disease caused by lack of insulin production in the pancreas or by insulin resistance, the disease being characterized by elevated blood glucose levels. Hyperglycemia in diabetes could lead to oxidative stress due to the rise in 8-oxo-2-deoxyguanosine (8-oxo-dG) levels and the decrease in levels of total antioxidant status (TAS). The purpose of this study was to assess the effect Aloe vera extract on 8-oxo-dG level and total antioxidant status in diabetic rat testis. MethodsThis was an experimental laboratory study with 20 rat samples which were divided into 4 groups (1 control group and 3 treatment groups). Diabetes was induced in the rats by streptozotocin (STZ) at 65 mg/kgBW. The diabetic rats were then treated for 28 days with Aloe vera extract at 0 mg (P0), 200 mg rind (P1), 200 mg pulp (P2), respectively. The level of 8 -oxo-dG was measured by ELISA and total antioxidant status with 2,2 -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS). Data were analyzed with ANOVA and Least Significant Difference Advanced Test at P<0.05. Results8-Oxo-dG levels were significantly different between the control group and both P0 and P2, but not between the control group and P1. Among the treatment groups the 8-oxo-dG levels were significantly different. Mean total antioxidant status was significantly different between control and treatment groups, and also between treatment groups (p<0.05). ConclusionsAloe vera extract reduced free radicals (level of 8-oxo-dG) and increased the total antioxidant status in diabetic rat testis.